Prevalence of Toxoplasma gondii Antibodies Among Workers Handling Fruits and Vegetables at Janzour Market, Libya (Journal of Medical Sciences, 2026)
Toxoplasma gondii infection remains a significant public health concern worldwide, particularly among occupational groups exposed to contaminated environments. Workers handling fruits and vegetables may be at increased risk due to contact with soil and unwashed produce; however, data from Libya are limited. This study aimed to determine the seroprevalence of T. gondii IgG antibodies and assess associated demographic and occupational risk factors among market workers in Janzour, Libya. A cross-sectional study was conducted among 57 male workers between July and August 2021. Sociodemographic and occupational data were collected using structured questionnaires, and serum samples were analyzed using a commercial ELISA kit. Associations were assessed using Fisher’s exact test, with p ≤ 0.05 considered significant. The results showed that 54.4% of participants were seropositive, indicating substantial prior exposure. Seroprevalence was highest among workers aged 45–59 years 2(66.7%) and 15–29 years 24(60.0%), although differences were not statistically significant. Nationality and soil exposure were not significantly associated with infection. In contrast, the type of produce handled showed a significant association, with fruit handlers exhibiting the highest prevalence 18(72.0%). travelers had significantly higher seropositivity compared to travelers. These findings highlight the need for improved hygiene practices, enhanced market sanitation, and targeted health education to reduce occupational exposure.